Systematics of the dipole polarizability - Brandherm Isabelle; von Neumann-Cosel Peter; Klaus Tobias; Matsubara Hiroaki; Pietralla Norbert; Tamii Atsushi (EPJ Web of Conferences)
The electric dipole polarizability is a key observable to set constraints to the symmetry energy parameters of the equation of state and the neutron skin thickness of nuclei. The electric dipole response of a nucleus can be probed with inelastic proton scattering at very forward angles and proton energies of several hundred MeV, where relativistic Coulomb excitation dominates. In the last decade, the electric dipole response in numerous nuclei has been measured at the Research Center for Nuclear Physics in Osaka, Japan. In this work new results about the dipole response and dipole polarizability of 58 Ni will be shown. The now available systematics of polarizability data will be discussed within the framework of the Migdal model.